Work patterns and occupational hazard exposures of North Carolina adolescents in 4-H clubs. Issue 4 (December 1996) - Cohen, L. R.; Runyan, C. W.; Dunn, K. A.; Schulman, M. D.
Abstract : OBJECTIVES: This study documents sex differences in work patterns, injuries, and hazard exposures among adolescents in homes, farms, and other work sites. METHODS: 14 to 17 year old 4-H club members were asked to complete self administered questionnaires regarding their lifetime experience of work, hazard exposure, and injuries. RESULTS: Of 323 respondents, more than two thirds had ever worked paid jobs. Fifty seven per cent were injured during non-farm work and hazards were part of the non-farm work environment for 54% of the respondents. Males were more likely to work in hazardous conditions, including operating heavy equipment on farms or construction sites. Almost three quarters of the teens who worked on farms reported being injured there and 100% were exposed to at least one farm hazard. CONCLUSIONS: Adolescents perform jobs at homes, farms, or other work sites where they are exposed to numerous safety hazards. Prevention efforts should target specific hazards youths are exposed to rather than the general work site.